Belajar dan Bermain Sebagai Metode Bimbingan Belajar Kepada Anak Gang Perwira di Kota Medan - Emmy Silvia Tarigan; Mia Aulina Lubis (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Education is the right of every child, and learning is something that should be done for children in building character and building human resources. However, many of the children in Gang Perwira themselves still have low interest in learning, and there are still many assumptions that learning is a boring activity, besides that they are still ignorant in capturing lessons at school. Due to their ignorance of the lessons at school, many children do not feel interested in their lessons at school, as well as the children in Gang Perwiras. Therefore, the existence of field work practicum activities (PKL) would help the process of tutoring children in Gang Perwira. Program interventions in this practicum are individual interventions by Skidmore, namely the research phase (Study Phase), the assessment phase, the planning phase, the intervention phase, and the termination phase. With this practicum, it is hoped that it can foster children's interest in learning.